Da multidão ao império: o ceticismo teórico de Antonio Negri - Rios, Valdir Lemos [UNIFESP] (2015)
With the end of World War II (1939-1945), two emerging powers would dispute the world hegemony by occasion of the Cold War (1947-1991): the United States, leading the capitalist conglomerate, and the Soviet Union, leading the socialist set. Soon after the period of Cold War, Empire, the book, creates a fuss in academic circles and in the media with their provocative theses. The authors of Empire advocate the end of imperialism, replaced by the rise of the empire, based on the central idea of the decline of the sovereignty of the nation state, and on the secondary concept of crowd. However, we consider that the emergence of the new political subject to which Hardt and Negri refer is the idea that the way to the empire and the nation-state sovereignty of the decline is a secondary assumption in their work. Such a perspective by Hardt and Negri, especially by the latter, comes as a result of his political experience when joining the Italian ?operarismo? movement during the 1970s and 1980s, a period when the concept of multitude was in a process of birth, and when a theoretical break lead him to his theoretical skepticism.